Prevalence of non-alcoholic fatty liver disease in overweight and obese children seeking ambulatory healthcare in Nairobi, Kenya. Issue 1 (16th February 2023) - Mburu, Anne Njeri; Laving, Ahmed; Macharia, William M; Sande, Joyce
Abstract : Background: While linked to obesity and associated with an increased cardiovascular morbidity, non-alcoholic fatty liver disease (NAFLD) is an often-asymptomatic cause of chronic liver disease in children. Early detection provides opportunity for interventions to curb progression. Childhood obesity is on the rise in low/middle-income countries, but cause-specific mortality data associated with liver disease are scanty. Establishing the prevalence of NAFLD in overweight and obese Kenyan children would guide in public health policies aimed at early screening and intervention. Objectives: To investigate prevalence of NAFLD in overweight and obese children aged 6–18 years using liver ultrasonography. Methodology: This was a cross-sectional survey. After obtaining informed consent, a questionnaire was administered, and blood pressure (BP) measured. Liver ultrasonography was performed to assess fatty changes. Categorical variables were analysed using frequency and percentages. χ 2 test and multiple logistic regression model were used to determine relationship between exposure and outcome variables. Results: Prevalence of NAFLD was 26.2% (27/103, 95% CI=18.0% to 35.8%). There was no association between sex and NAFLD (OR1.13, p=0.82; 95% CI=0.4 to 3.2). Obese children were four times more likely to have NAFLD compared with overweight children (OR=4.52, p=0.02; 95% CI=1.4 to 19.0). About 40.8% (n=41) had elevated BP, but there was no association with NAFLD (OR=2.06; p=0.27; 95% CI=0.6 to 7.6). Older children (13–18 years) were more likely to have NAFLD (OR 4.42; p=0.03; 95% CI=1.2 to 17.9). Conclusion: Prevalence of NAFLD was high in overweight and obese school children in Nairobi. Further studies are needed to identify modifiable risk factors to arrest progression and prevent sequelae.